P280 A nudge in the right direction: can a poster increase use of buscopan during colonoscopy?. (19th June 2022) - Smith, Alastair; Fletcher, Martin; Walker, Gareth
Abstract : Introduction: BSG guidance states that intravenous (Hyoscine Butylbromide) Buscopan administration during colonoscopy may increase polyp detection, but should be avoided in patients with significant cardiac comorbidity 1 . "Nudge strategies" may influence automatic behaviour by targeting subconscious routines that are present in human decision-making. We assessed if a simple poster advocating safe use of buscopan during colonoscopy could influence endoscopist prescribing behaviour and if this behaviour persisted after poster removal. Methods: Posters were displayed for 120-days in all 4 endoscopy rooms at Torbay Hospital, a district general hospital in Southwest England, before being removed. We included all diagnostic colonoscopies in adults (>18 yrs old) and excluded tests performed by the study authors. Data were extracted electronically from our endoscopy database (Medilogik EMS) and analysed in R-Studio (4.1.2). Fisher's Exact analyses compared the proportion of colonoscopies with buscopan administered during equal time periods: firstly, before (01/02/2021 to 01/06/2021) vs during (01/06/2021 to 29/09/2021) poster display; and, secondly, during vs after (29/09/2021 to 27/01/2022) poster removal. Multivariable logistic regression analyses compared the association between: firstly, buscopan use and poster display period; and, secondly, polyp detection and buscopan use, after including other clinically relevant covariates. Results: The proportion of colonoscopies with buscopan administered increased during poster display (24% [259/1097] before vs 41% [496/1213] during poster display, P<0.0001]; and did not change following poster removal (41% [496/1213] during vs 44% [539/1222] after poster display, P=0.1). Multivariable analyses demonstrated: firstly, that the poster display period was associated with a 2-fold increase in odds of buscopan administration (odds ratio[OR]=2.2, 95%CI 1.9-2.7, P<0.0001) independent of age and cardiac comorbidities; and secondly, that buscopan administration was associated with a 2-fold increase in polyp detection (OR=1.6, 95%CI 1.3-2.0, P<0.0001) independent of patient age, sex and number of colonoscopies performed by endoscopist in last 12 months. There was no difference in adverse events before (0% [0/1097]) and during poster display (0.8% [1/1213])(P=1.0). Conclusions: We demonstrated that a simple poster can safely influence endoscopist buscopan prescribing behaviour and that this effect was maintained after the poster removal. We confirmed the association between the use of buscopan during colonoscopy and improved polyp detection. 1) BSG guidance on the use of intravenous buscopan during gastrointestinal endoscopy.